Metal-ceramic dowel crown restorations for severely damaged teeth: A clinical report - Yuzugullu Bulem; Canay Senay (Wolters Kluwer Medknow Publications, 2009)
This clinical report describes an alternative prosthodontic treatment of a patient who had severely damaged endodontically-treated first molar teeth in all quadrants of her mouth. The young patient′s severely damaged permanent molar teeth were treated with a restoration combining the advantage of the esthetics of dental porcelain, reinforced with the underlying cast gold dowel crown. Using this technique, the remaining sound tooth structure was preserved with function and esthetics accomplished. The described metal-ceramic one piece dowel crown restoration seemed to perform without any problems for the 12 month evaluation time.